Comparative analysis of information on radiation accidents in the Russian Federation in 2010–2022 - A. V. Gromov; R. R. Akhmatdinov; A. M. Biblin; O. E. Tutelyan (Радиационная гигиена)
We have summarized, analyzed and assessed data on radiation accidents and incidents that occurred on the territory of the Russian Federation for the period from 2010 to 2022. The data are presented in the Data bank of radiation accidents and incidents of the Information and Analytical Center of Rospotrebnadzor on radiation safety, in the form of federal statistical observation No. 18 “Information on the sanitary condition of the subject of the Russian Federation”, and in radiation-hygienic passports of territories. The objective of the study was to conduct a comparative analysis of information on radiation accidents for the period from 2010 to 2022 contained in the above-mentioned sources. The objective of the study was to perform a comparative analysis of information on radiation accidents for the period from 2010 to 2022 contained in the above-mentioned sources. Comparison of the number of radiation accidents in dynamics has shown the presence of discrepancies between the studied data sources, lack of systematicity of these discrepancies, and multidirectional trends in the number of radiation accidents. From 2010 to 2022, in the Data bank of radiation accidents and incidents of the Information and Analytical Center of Rospotrebnadzor on radiation safety were registered 2,690 cases of radiation accidents in 71 subjects of the Russian Federation, in Forms No. 18 – 2,469 cases in 67 subjects, in radiation-hygienic passports of territories – 2,457 cases in 76 subjects. Differences in the structure of data provision have been established: in the data bank and Form No. 18 radiation accidents are classified, but at the same time the principles of classification coincide partially; there is no classification in the radiation-hygienic passport of territories. The analysis showed that no information on radiation accidents was received from four regions during the study period. Among the subjects that provided information, only six regions have coincidence of data on all sources. Some regions were identified where information was provided to some data bases but not to others. In five regions, a range of more than 50 cases was detected; the coefficient of variation in the number of radiation accidents between sources exceeded 33% in 53 subjects. The identified discrepancies demonstrate the lack of a systematic approach to the procedure for providing information on radiation accidents, which may be related to the failure to fully comply with the requirements for providing information to Rospotrebnadzor and the St. Petersburg Research Institute of Radiation Hygiene after Prof. P.V. Ramzaev, contradictions in the list of information to be provided in Rospotrebnadzor’s offices, and difficulties in determining by Rospotrebnadzor’s offices in the subjects of the Russian Federation what information is to be reported in this or that form of statistical observation.